Feminist Religious Guidance and Its Contemporary Applications: An Objective Qur’anic Study: الإرشاد الديني النسوي وتطبيقاته المعاصرة: دراسة موضوعية قرآنية - Yousuf Ibrahim al-Sarhania, Aesha; Ahmad Abdallah Abu-Alhaj, Thabet; Amir, Selamat; al-Majali, Mohammad Khazer (Jurnal Usuluddin, 2025)
This study seeks to highlight the importance of women’s religious guidance within educational institutions through a Qur’anic methodology. It aims to identify Qur’anic verses that affirm the role of Muslim women in Da‘wah and to clarify key contemporary methods of religious guidance. The research problem is reflected in the increasing prevalence of deviant behaviors among female students in educational institutions, resulting from weak religious awareness, the marginalization of Muslim women’s role in guidance, and the absence of a systematic vision for activating religious guidance. The study adopts an inductive approach to survey relevant texts, a descriptive-analytical method to examine Qur’anic verses emphasizing women’s role in Da‘wah, and an applied approach based on interviews with female religious guides. The findings confirm that Muslim women’s participation in Da‘wah is authentic and firmly rooted in the Holy Qur’an, and that religious guidance is a continuous responsibility across all times and places. Furthermore, the results demonstrate that activating a systematic model of women’s religious guidance contributes to building faith-based and critically aware generations capable of confronting intellectual deviation, protecting society, and strengthening it in accordance with the Qur’anic methodology.